The Problem of Freedom in Education versus Social Solidarity and Self-creation—the Context of the Postliberal Philosophy of Education - Michałowska, Danuta Anna (Sensus Historiae, 2023)
The aim of the paper is to present the outline of problem of freedom in education from a liberal point of view and problems in achieving the educational goals regarding to the development of social solidarity and the process of autonomy and self-creation of the individuals. Worldview values and their certain varieties, i.e. moral values, constitute a perspective for defining the contemporary functions of ethical education at school. The context of consideration refers to the post-liberal philosophy of education—the philosophy of student-centered education—one who belongs to a community of autonomous individuals.